Rural Livelihoods and Income Resilience in Northern Nigeria During Covid-19: A Generalized Heckman and Generalized Ordered Probit Approach - Oyekale, Abayomi Samuel (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2026)
Purpose: This study examined the effect of livelihood sources on rural income and its sustainability in northern Nigeria, particularly within the context of conflict and the COVID-19 pandemic. It aimed to determine how different livelihood engagements influence income levels and income sustainability among rural households. Design/Methodology/Approach: The study utilized panel data from Rounds 1 and 2 of the Data in Emergency (DIEM) surveys conducted by the Food and Agriculture Organization (FAO) in 2021 and 2022. The analysis employed Ordered Probit, Generalized Ordered Probit, Tobit, and Generalized Heckman regression models to assess the determinants of income changes and sustainability across livelihood categories. Findings: The results revealed that crop farming (35.74%) and livestock farming (34.27%) were the dominant livelihood sources. About 32.94% of households experienced slight income reductions, while 30.30% reported slight income increases. The Generalized Heckman results indicated that income significantly increased (p<0.05) among households engaged in crop farming, livestock farming, and mixed crop-livestock activities, as well as among those with basic and higher education. The Generalized Ordered Probit model showed that income sustainability was significantly (p<0.05) enhanced by residence in Bono, Katsina, and Zamfara states, attainment of basic and higher education, being unaffected by COVID-19, and engagement in crop-only and mixed crop-livestock farming. Originality/Value/Novelty: This study provides empirical evidence on the role of livelihood diversification and education in promoting income resilience and sustainability during periods of health crises and conflict in northern Nigeria. By integrating pandemic-related shocks with livelihood analysis using advanced econometric models, it contributes to policy discussions on strengthening rural income stability through agricultural promotion and access to formal education.